Giving a fish or teaching to fish? Exploring the effects of home-country governmental support on foreign exit decisions. Issue 6 (18th June 2020) - Tan, Qun; Sousa, Carlos M.P.
Abstract : Purpose: To help firms with their international operations, governments often create policies and support mechanisms, but its influence on the firm's exit decision has so far been ignored. Hence, the purpose of this study is to examine the impact of home-country governmental support on the firm's exit decision. Design/methodology/approach: The authors test their conceptual model using multiple informants as well as secondary data from China. The sample consists of 360 valid questionnaires from 180 firms. Binary logistics regression is used to test the conceptual framework. Findings: By demonstrating that resource-based and institutional constructs are highly dependent, the authors show how home-country governmental support interacts with the foreign affiliate's past performance to explain the decision to remain or exit a foreign market. The results indicate that while governmental financial support reduces the likelihood of exiting a poorly performing business in the foreign market, governmental non-financial support surprisingly has an opposite effect. Originality/value: While there has been an increasing number of firms exiting foreign markets, this area of research is still limited. The study also contributes to the literature by focusing on home-country governmental financial and non-financial support to explain the firm's exit decision – an issue that has been ignored and is expected to be particularly relevant for firms from emerging economies.